Perjumpaan Dengan Allah: Iman, Harapan, dan Kasih Menurut Santo Yohanes Dari Salib - Alnija, Marianus Dinata; Lektawan, Fedrianus Korintius (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
This research investigates the perspective of Saint John of the Cross regarding encounters with God through the lenses of Faith, Hope, and Love, as elucidated in the renowned work titled "The Impact Of God" authored by Iaian Matthew. The purpose of this study is to examine the influence of these encounters on an individual's spiritual existence. The research employed methodologies such as literature review and textual analysis. The findings of this investigation reveal that faith, hope, and love serve as pivotal avenues for encountering God. Through enriching the spiritual experiences of individuals and guiding them towards a deeper comprehension of the divine, these encounters engender substantial transformation. According to Saint John of the Cross, faithfulness in faith, unwavering hope, and profound love are indispensable prerequisites for attaining an intimate encounter with God. This article underscores the significance of encountering Allah in these three dimensions and highlights its profound impact on an individual's life. Consequently, a profound understanding of encountering God through Faith, Hope, and Love can serve as a wellspring of inspiration for individuals seeking to nurture their spiritual journey.